Electrochemical Impedance Spectroscopy (EIS) study of coconut water as natural inhibitor in Malay traditional preservation of iron artefact - Musa, Mukhtaruddin; Purwanto, Hadi; Abdul Razak, Rajabi; Othman, Raihan; Musa, Lukman; Ani, Mohd Hanafi (IOP Publishing Ltd, 2020)
Treating and cleaning corroded artefact has resulted in long-term loss of artefact integrity and intangible historical value in museum preservation method. Inhibitors and coatings are preferable methods applied in heritage conservation as it is the easiest way for corrosion protection. However, issue of health and environment has led conservators to find a better inhibitor, natural or green corrosion inhibitors. Surprisingly, Malay traditional practice has since long ago used Coconut water (CW) as corrosion inhibitor to preserve keris blades, showing that the knowledge in corrosion protection has been practiced in old Malay civilization for metal preservation. This paper intends to clarify the compositional effect of CW in the inhibition efficiency to iron-based keris blade. Through Tafel and Electrochemical Impedance Spectroscopy (EIS) and Energy dispersive analysis of X-rays (EDAX) analysis, the study showed that CW formed passivation with the highest IE of 92% as compared to other natural inhibitors existing and used in industries such as Ascorbic Acid (AA) and Tartaric acid (TA). EIS and Scanning Electron Microscope (SEM) study has shown and conclude that CW has displayed protective abilities that exceeds both AA and TA.